The Body in Education: The Cognitive and Phenomenological Perspective - Volkova, Svetlana (Voprosy obrazovaniya / Educational Studies Moscow, 2017)
The article reflects one of the main tendencies in philosophy of education, the so-called “corporeal turn”. An attempt is made to analyze the key ideas of Maurice Merleau-Ponty’s phenomenology and the latest achievements in cognitive research in their relationship with the phenomenon of education. The ideas of cognition as a process of producing mental representations, body and mind dichotomies and the value priority of the latter over the former are criticized. Justification is provided for the idea that the mind executes its cognitive processes using epistemic resources that emerge and are congruent with activities, needs and goals of the body. Thus, the mind is not restricted to one “place”, rather being distributed across a network of interactions between mental, sensory and motor processes. The appeal to the lived body experience is extremely important as it reveals the meanings that students focus on in their learning activity, thus making intersubjective relationships more transparent. The explication of the idea of unity of body and mind will allow educators to adequately determine the role and place of corporeity in both perception and thought processes and eventually discover new cognitive and phenomenological strategies for substantiating the significance of such disciplines as drama and dance, music and physical education in the educational process.